Elevated CO2 and Nitrogen Interaction in Photosynthesis and Productivity of Modern and Local Rice (Oryza sativa L.) Cultivars - Razzaque, MA; Haque, M Moynul; Hamid, A (The Agriculturists, 2010)
Photosynthetic rate and productivity of modern and local rice (Oryza sativa L.) cultivars were compared at different levels of nitrogen and elevated CO2 concentrations. BRRIdhan 39 and Shakkorkhora representing modern and local cultivars, respectively were tested under the conditions of three nitrogen levels and three CO2 concentrations. Nitrogen levels were (i) control (0 kg N ha-1), (ii) optimum (90 kg N ha-1 for modern and 60 kg N ha-1 for local cultivar) and (iii) supra optimum (135 kg N ha-1 for modern and 90 kg N ha-1 for local cultivar). Conversely, the three CO2 concentrations were (i) open top chamber (OTC) with elevated CO2 (570 ± 50 ppm), (ii) OTC with ambient CO2 (~360 ppm) and (iii) open field. It was observed that the elevated CO2 independently increased the photosynthetic rates in both cultivars. While in interaction, elevated CO2 and supra optimal nitrogen increased the photosynthetic rate in modern rice cultivar only. Productivity of two rice cultivars corresponded to that of photosynthetic rates. The highest yield (50.82 g plant-1) was found in modern cultivar at supra optimal nitrogen and elevated CO2 treatments. In contrary, the lowest yield (15.09 g plant-1) was observed in local cultivar at zero kg nitrogen treatment. However, productivity of local rice cultivar was substantially increased either by applied optimum nitrogen or by CO2 enrichment.